ANALYSIS AND IDENTIFICATION OF THE PUBLIC AND PRIVATE MARKET SHARE OF INSURANCE PREMIUM CHARGEABLE AND PAYABLE AND FORECASTING OF THIS FINANCIAL MARKET - reza izadi, Hamid; Izadi, Maryam (European Scientific Journal, ESJ, 2013)
Abstract text, By delivering service to and establish reasonable relationships with other industrial, manufacturing, agricultural and service sectors through collecting small insurance premiums from insureds, and indemnifying timely, the insurance industry as a non-banking financial institution can raise public and private capitals, efficiently direct and invest such financial resources, secure production by entrepreneurs, business owners, and professionals, reduce imports from and dependence upon global markets, and hence lead to economic development. Therefore, identification of the public and private shares of this financial market can have a substantial effect on saving financial resources. Moreover, forecasting of this financial market in respect to insurance premiums chargeable and payable and controlling and directing such financial resources can help different economic sectors make investments and implement their monetary and financial policies in order to reach their long term economic goals. Therefore, this study has attempted to analyze and forecast insurance market by ARIMA model and stability test.